Upaya Peningkatan Minat Belajar Pendidikan Agama Islam dengan Metode Snowball Throwing di SMK Bina Karya 1 Karanganyar Kelas XI Multimedia - Gilang Ramadhan; Ilham Nur Handoko; Muhammad Chaidar Ma’ruf; Siti Fatimah; Fuad Hasyim (IAINU Kebumen, 2023)
This increase aims to determine the increase in student learning interest at SMK Bina Karya 1 Karanganyar Kebumen in Islamic Islamic Education and Moral Subjects in the subject matter of Modern Islamic Civilization. The learning method applied as an effort to increase student learning interest is the Snowball Throwing method (bola-bola salju). The research was conducted in two cycles with two meetings in each cycle. In cycle one, the initial data obtained in the first meeting of students' learning interest was 58%, then the second meeting of cycle one had experienced a slight increase in learning interest to 72%. However, in this first cycle, it did not meet the success indicator criteria for Classroom Action Research, namely at least 75%. After completing cycle I, the researcher reflected on the learning process to increase student interest in learning, then made improvements for meetings in cycle II. After the second cycle was carried out, the first meeting obtained an increase in student learning interest to 78%. This means that in this cycle it meets the success criteria of the applied learning method. However, researchers need to ensure that the learning methods applied are successful in increasing students' interest in learning, so the researchers continued until the second meeting of cycle II, and the results also increased quite well to 88%. These results indicate that the Snowball Throwing learning method succeeded in increasing students' interest in learning at SMK Bina Karya 1 Karanganyar class XI Multimedia in Islamic Education subject matter of Modern Islamic Civilization based on the results of classroom action research that had been carried out.